Integrating certifications into the cybersecurity college curriculum: The efficacy of education with certifications to increase the cybersecurity workforce - Binh Tran; Karen C. Benson; Lorraine Jonassen (Journal of Cybersecurity Education, Research & Practice)
One only needs to listen to the news reports to recognize that the gap between securing the enterprise and cybersecurity threats, breaches, and vulnerabilities appears to be widening at an alarming rate. An un-tapped resource to combat these attacks lies in the students of the secondary educational system. Necessary in the cybersecurity education is a 3-tiered approach to quickly escalate the student into a workplace-ready graduate. The analogy used is a three-legged-stool, where curriculum content, hands-on skills, and certifications are equal instruments in the edification of the cybersecurity student. This paper endeavors to delve into the 3rd leg of the stool by developing the concept of vendor-specific and vendor-neutral certifications to educate the cybersecurity student and test their capability of protecting the workplace. The research data was drawn from companies in the Atlanta, Georgia area, who employ and hire cybersecurity recruits. The data from the research proves certifications are necessary as an addition to the cybersecurity curriculum in the secondary education arena. The paper reviews the need for cybersecurity graduates, the balance between cybersecurity theory and applied skillsets, the difference between a certificate and a certification, benefits to the community, classifications of certifications, relevancy of a college degree in today’s workforce, and recommendations for further study.